Analisis Perancangan dan Implementasi FHRP di Protokol Routing RIPv2 dan OSPF - Ramdhani Syahputra; Rahmadi Kurnia; Rian Ferdian (Ikatan Ahli Informatika Indonesia (IAII), 2020)
The high reliability of data access has become a problem faced by many companies, institutions, and universities. For this reason, a protocol required that can protect the network from a communication breakdown. One method used to maintain communication is by implementing a protocol redundancy system. One or more routers will act as the primary router for load balancing, and some routers are in standby mode if one main router is down. First hop redundancy protocols (FHRP) is a protocol that implements redundancy and load balancing systems. This protocol can transfer access data traffic if one of the routers on the network is down. FHRP divided into virtual router redundancy protocol (VRRP) and gateway load balancing Protocol (GLBP). This research analyzes the design and implementation to provide information about the quality of VRRP and GLBP services on the main router and the backup router, by using an application graphical network simulator (GNS) simulation 3. In the GNS3 application, a LAN network topology is designed with eight router devices in the form of a ring topology using RIPv2 and OSPF routing protocols, then implemented in protocols VRRP and GLBP. The analysis results show that GLBP can back up the network faster than VRRP when the primary router is down. If implemented into a LAN network with RIPv2 and OSPF routing protocols, VRRP has better service quality than GLBP.